El amor como transformación en el amado: meditación sobre un pasaje del Comentario de Santo Tomás a las Sentencias - Berro, Alberto (Sapientia, 2021)
Here is a meditation on a stupendous passage by Saint Thomas on love in the Commentary on the Sentences of Pedro Lombardo, III, d. 27, Q. 1 am 1 C. In the context of the theme of Charity, Tomás explains to us what happens ontologically every time a person loves another with the love of friendship. What happens is a true transformation of the lover into the beloved, from the reception of his form in the spiritual affective power, that is, in the will, in a certain analogy with what happens with the knowledge of the other. . Starting from this central thesis, the author breaks down the consequences of love in the lover, insofar as love makes us one with the beloved and moves the lover to act accordingly, with full delight, breadth and energy.